Impact of Holding on Financial Performance and Governance: Evidence From Indonesia’s State-Owned Enterprise - Simbolon, Ramadona; Elviani, Sri; Gustarina, Elina Rahmawati; Octavianika, Ika; Kinsky, Carina (International Journal of Economics Studies, 2025)
This research examines the influence of holding on the financial performance and governance of State-Owned Enterprise (SOE) carrying out holding companies. Paired t-test is used to examine the influence of holding on the financial performance and governance of State-Owned Enterprise (SOE) carrying out holding companies. This research reveals that the holding has a positive effect on the current ratio, but has no effect on ROA and ROE. Furthermore, this research reveals that holding companies have a negative effect on DER and BOPO. Apart from that, this research has a positive effect on the composition of independent commissioners but has no impact on the size of commissioners. This research confirms that holding contribute in the short term on financial performance and governance. The findings this study plays an important role in optimizing financial performance and strengthening SOE governance. This research also provides suggestion for SOE Management to prepare long term strategies, so that the holding company’s business objectives can be achieved. This research contributes to existing literature, by highlighting the financial performance, governance and SOE in Indonesia.